The role of infected epithelial cells in Chlamydia-associated fibrosis - Caven, Liam T.; Carabeo, Rey A. (Frontiers in Cellular and Infection Microbiology, 2023)
Ocular, genital, and anogenital infection by the obligate intracellular pathogen Chlamydia trachomatis have been consistently associated with scar-forming sequelae. In cases of chronic or repeated infection of the female genital tract, infection-associated fibrosis of the fallopian tubes can result in ectopic pregnancy or infertility. In light of this urgent concern to public health, the underlying mechanism of C. trachomatis-associated scarring is a topic of ongoing study. Fibrosis is understood to be an outcome of persistent injury and/or dysregulated wound healing, in which an aberrantly activated myofibroblast population mediates hypertrophic remodeling of the basement membrane via deposition of collagens and other components of the extracellular matrix, as well as induction of epithelial cell proliferation via growth factor signaling. Initial study of infection-associated immune cell recruitment and pro-inflammatory signaling have suggested the cellular paradigm of chlamydial pathogenesis, wherein inflammation-associated tissue damage and fibrosis are the indirect result of an immune response to the pathogen initiated by host epithelial cells. However, recent work has revealed more direct routes by which C. trachomatis may induce scarring, such as infection-associated induction of growth factor signaling and pro-fibrotic remodeling of the extracellular matrix. Additionally, C. trachomatis infection has been shown to induce an epithelial-to-mesenchymal transition in host epithelial cells, prompting transdifferentiation into a myofibroblast-like phenotype. In this review, we summarize the field’s current understanding of Chlamydia-associated fibrosis, reviewing key new findings and identifying opportunities for further research.